Charakterystyka budowy ciała tancerzy stylu standardowego tańca sportowego na przykładzie pary mistrzów świata = Characteristics of body building standard style dancers on the example of pair of world champions - Pilewska, Wiesława; Sech, Patrycja; Pilewski, Robert (Journal of Education, Health and Sport, 2015)
Pilewska Wiesława, Sech Patrycja, Pilewski Robert. Charakterystyka budowy ciała tancerzy stylu standardowego tańca sportowego na przykładzie pary mistrzów świata = Characteristics of body building standard style dancers on the example of pair of world champions. Journal of Education, Health and Sport. 2015;5(11):565-576. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35698 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A565-576 http://pbn.nauka.gov.pl/works/684768 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Original Text published © The Author (s) 2015. Pilewska Wiesława, Sech Patrycja, Pilewski Robert. Charakterystyka budowy ciała tancerzy stylu standardowego tańca sportowego na przykładzie pary mistrzów świata. Quality in Sport. 2015;1(1):55-65. eISSN 2450-3118. The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland. Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.11.2015. Revised 20.11.2015. Accepted: 30.11.2015. Wiesława Pilewska, Patrycja Sech, Robert Pilewski Instytut Kultury Fizycznej, Uniwersytet Kazimierza Wielkiego w Bydgoszczy Charakterystyka budowy ciała tancerzy stylu standardowego tańca sportowego na przykładzie pary mistrzów świata Characteristics of body building standard style dancers on the example of pair of world champions Streszczenie Cel pracy Celem pracy było określenie specyfiki budowy somatycznej tancerzy sportowego tańca towarzyskiego stylu standardowego. Materiał Materiał badawczy stanowiła para sportowego tańca towarzyskiego posiadająca najwyższą, międzynarodową klasę taneczną „S”. Mistrzowie Świata z 2013 roku w stylu standardowym. Długość stażu tanecznego pary wynosiła 19 lat. Badane osoby trenowały od 6 do 7 dni w tygodniu, po 3-4 godziny dziennie. Oboje mieli po 28 lat. Metoda Oceny rozwoju fizycznego dokonano na podstawie pomiarów antropometrycznych masy i wysokości ciała, długości szyi, kończyn górnych i dolnych, tułowia, uda i podudzia, długości stopy, szerokości barków, miednicy, stopy, klatki piersiowej, głębokości klatki piersiowej, obwodów talii, bioder, uda oraz podudzia. Na ich podstawie obliczono wskaźniki budowy ciała. Wykorzystano również klasyfikacje typologiczną dla oceny specyfiki budowy ciała badanych osób. Wnioski Para sportowego tańca sportowego stylu standardowego o wysokim poziomie sportowym (Mistrzowie Świata z 2013r.) charakteryzowała się specyficzną budową somatyczną przejawiającą się określoną wielkością cech i wskaźników budowy ciała. Prezentowane wielkości parametrów cech somatycznych i wskaźników morfologicznych należy traktować jako wynik wymagań stylu standardowego sportowego tańca, osobno dla tancerzy i tancerek a także wspólnie dla pary tanecznej jako specyfika ich doboru oraz wpływ treningu tanecznego na kształtowanie się ich somatotypu. Słowa kluczowe: taniec towarzyski, styl standardowy, budowa somatyczna, mistrzowie świata. Abstract Aim of the study The aim of the study was to determine the specificity of somatic build ballroom dancers sporting standard style. Materials The research material was sporting ballroom dancing couple having the highest international dance class "S". World Champions of 2013, the standard style. The length of the internship dance couples was 19 years. Subjects were trained from 6 to 7 days a week, after 3-4 hours a day. They were both 28 years. Methods Physical development assessment was based on anthropometric measurements of body weight and height, the length of the neck, upper and lower limbs, torso, thigh and lower leg, foot length, width, shoulders, pelvis, feet, chest, deep chest, circuits, waist, hips, thighs and ankles. Typological classification was also used to assess the specificity of physique subjects. Conclusions A pair of dance sport sporty style with a high level of standard sports (with the 2013 World Champions.) characterized by a specific construction of somatic manifested a certain size characteristics and indicators of body (shown in this work).Presented by their size parameters of somatic and morphological indicators should be considered as a result of the impact of dance training and the requirements of the standard style of discipline and separately for dancers and dance together for a couple as the specifics of their selection. Key words: ballroom dancing, standard style, construction somatic, World Champions.